Applications of Mathematical Optimisation to Non-Functional Requirements in Software Engineering - Affleck, Amy (Curtin University, 2016)
The neglect of non-functional requirements is a leading contributor to project failure. Current work within goal-oriented requirements engineering focuses on the evaluation of techniques designed to address non-functional requirements. This thesis investigates transition from evaluation algorithms to decision algorithms, through the use of mathematical optimisation, specifically Mixed Integer Linear Programming. Optimisation schema are presented for both the NFR Framework and GRL. The schemas are assessed based on scalability, consistency, and automation.